Melewar buddyz bibliotherapy - Ahmad, Asma’; Ahmad, Muhamad Dom; Shari, Siti Aida; Shahruddin, Sri Diah (Universiti Teknologi Mara, Kedah, 2023)
Libraries in educational institutions, including schools and teachers' educational institutions, need to keep pace with the needs of the 21st century. Today, periodicals and print books are not the only available resources. The essential element of the Library of Tomorrow, which creates a space for all, has been widely practised in Malaysia. When mentioning a library, a close image with it is books. Books are closely related to scientific culture. In the Al-Quran, the first Ayah Al Quran to Prophet Muhammad SAW, (PBUH), it is the word Iqra' in Surah Al Alaq, (AlQuran), which means Read (S.S Datuk Dr. Zulkifli Bin Mohamad Al-Bakri, 2016) This Surah Al-Alaq explains that Allah SWT created man and glorified him by teaching him to read, write and give him knowledge (Khairul Asyraf & Mohd Sukki, 2021). Books also serve as therapy material for counselling clients. Bibliotherapy or bibliotherapy comes from the Greek word biblus, which means book. At the same time, the word therapy or therapy refers to psychological help (Crenshaw., 2010). Bibliotherapy is now necessary, as the world of information is based on reading, both in print and digital form (Asep Solikhin, 2015). Furthermore, since the outbreak of the COVID-19 pandemic, which the WHO announced in March 2020 (World Health Organization, 2020), the statistical increase in mental health cases every year shows the need for the empowerment of existing prevention efforts (Shahril Nizam Zulkipli, 2023) The Biblio-Counseling approach is seen as a reading material technique that is chosen to form a more positive self-development and student personality. In addition to reading books in print media, this method is also through reading in digital media. The researcher also developed an online reading method. As a result, the study school's increased students passed 100% in Bahasa Melayu and Sijl Pelajaran Malaysia History 2022. This module has been applied in two secondary schools in Seremban, Negeri Sembilan and Arau, Perlis. This approach was also shared with the Education Technology Resource Sector Officer of the Perlis State Education Department in 2022, Brunei Darus Salam in 2019 and the Negeri Sembilan Education Department in August 2023. This approach forms a positive self-concept, increases motivation, relieves emotional stress and boredom, discusses problems openly, explores various options for solving problems and gives students common sense. In conclusion, let us all take the spirit of the first verse al-ayah from Al Quran Al Kareem, the revelation which is Iqra' (Read) (AlQuran). Hence, it has become a culture for us to step forward in studying and gaining as much knowledge as possible.